Evectiveness of the DASH Diet for Controling Stage 1-2 Hypertension in Developing Countries : A Scoping Review - Rahmat Hidayat; Rismanudin Rismanudin; agus salim (An Idea Health Journal, 2025)
Introduction: Hypertension remains a significant public health concern and is a leading risk factor for cardiovascular morbidity and mortality, especially in developing countries where uncontrolled blood pressure rates are elevated. Non- pharmacological interventions, such as dietary modification, are increasingly recognized as cost-effective strategies for hypertension management. Objective: This scoping review aims to map and synthesize the evidence on the role of dietary modification in hypertension management and control. The Dietary Approaches to Stop Hypertension (DASH) diet has shown substantial blood pressure–lowering effects in high-income countries; however, its effectiveness, feasibility, and implementation in developing countries have not been comprehensively reviewed. The objective of this scoping review is to identify, synthesize, and describe the available evidence on the effectiveness of the DASH diet in controlling stage 1–2 hypertension in developing countries. Methods: The review was conducted following the Joanna Briggs Institute (JBI) methodology and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). A scoping literature search was undertaken across multiple electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar. Studies assessing the DASH diet in relation to blood pressure outcomes, dietary adherence, or cardiometabolic indicators were included. Data were charted and synthesized descriptively based on study characteristics, populations, and key outcomes. Results: Adherence to the DASH diet was consistently linked to clinically significant reductions in systolic and diastolic blood pressure among individuals with stage 1–2 hypertension. Several studies also documented improved dietary adherence through community-based and culturally adapted interventions, particularly in low-resource settings. Positive effects on metabolic outcomes, including markers of obesity, metabolic syndrome, and inflammation, were observed across diverse population groups. Conclusion: The findings underscore the importance of dietary adherence, cultural adaptation, and community-based implementation to optimize effectiveness. These results support integrating the DASH dietary pattern into public health strategies and primary care services in resource- limited settings. Future research should prioritize long-term outcomes, culturally adapted DASH models, and large-scale implementation studies to enhance the evidence base and inform policy development.